Next-generation sequencing yields the complete mitochondrial genome of the Shangrila hot-spring snakes (Thermophis shangrila; Reptilia: Colubridae). Issue 1 (1st January 2017) - Wu, Wei; Jiang, De-Chun; Sun, Feng-Hui
Abstract: In this study, we sequenced the complete mitochondrial genome of Thermophis shangrila by using the next-generation sequencing technique. The total length of the mitogenome was 17, 407 bp, which was composed of 13 protein coding genes, two rRNA genes (12s and 16s rRNA), 22 tRNA genes, and two control regions (CRI and CRII). The base composition was 32.6% for A, 23.9% for T, 30.0% for C, and 13.5% for G. We added a fragment about 150 bp in length at control region I, which Peng et al. failed to obtain using Sanger dideoxy sequencing.